Aplicación web para la gestión de voluntarios en la organización crecer utilizando software libre - Bonilla Arciniega, Joseph Daniel (2024)
In an era where technological advancements are reshaping various facets of healthcare, the need for efficient management solutions within organizations like CRECER, dedicated to enhancing the lives of individuals with special needs, becomes increasingly apparent. This project sets out to address this need by developing a web-based application specifically tailored to optimize volunteer management processes within CRECER. Through the aggregation of data, streamlined user administration, and the generation of insightful reports, the application seeks to revolutionize volunteer management, ultimately enhancing organizational efficiency and effectiveness. Employing an applied research methodology, this study involves a comprehensive analysis of the existing system and the proposed technological solution. Through interviews, surveys, and direct observations, valuable insights from users and contextual factors are gathered to inform the development process. The research methodology focuses on understanding the intricacies of volunteer management within CRECER, ensuring that the resulting software meets the specific needs and requirements of the organization. The methodology emphasizes rigorous data coding, tabulation, analysis, and interpretation to derive meaningful conclusions. By systematically examining the current system's components and relationships, as well as identifying potential improvements, the research lays the groundwork for the development of an effective volunteer management solution. Anticipated outcomes include the successful implementation of a user-friendly software solution that significantly improves volunteer management processes at CRECER. This project underscores the potential of technology to positively impact organizational efficiency and effectiveness in the realm of volunteer management within nonprofit organizations.